Customer Loyalty Revisited: A Mediation Moderated Analysis of Perceived Value, Customer Satisfaction, And Café Atmosphere - Ikramuddin Ikramuddin; Mariyudi Mariyudi; Ghazali Syamni; Rico Nur Ilham; Sariyulis Terfiadi; Em. Yusuf Iis (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to explore how perceived value influences customer loyalty, with customer satisfaction acting as a mediating variable and café atmosphere as a moderating factor. Research Methodology: A quantitative research method was used. Data were gathered using self-administered questionnaires distributed at the cashier desk of a café in Lhokseumawe, Indonesia. A total of 190 customers were selected using convenience and intercept sampling techniques. Conditional process analysis was used to assess the direct, mediating, and moderating relationships among the variables. Results: The results revealed that perceived value significantly and positively affected both customer satisfaction and loyalty. Customer satisfaction has a strong positive impact on customer loyalty and partially mediates the relationship between perceived value and loyalty. Furthermore, the café atmosphere significantly moderates the relationship between customer satisfaction and loyalty, indicating that a more pleasant atmosphere enhances this connection. Conclusions: This study shows that perceived value enhances loyalty through customer satisfaction, with the café atmosphere strengthening these relationships. Limitations: This study's limitations include the fact that it was limited to the city of Lhokseumawe and did not differentiate between café sizes. Contributions: This study provides an integrated view by combining perceived value, customer satisfaction, and café atmosphere within a moderated-mediation framework. This study contributes to the understanding of customer loyalty formation, particularly in the café industry, both theoretically and practically.